MICRO-CELEBRITIES’ CONCEPT OF HIJRAH: A CRITICAL METAPHOR ANALYSIS - Zainur Rofiq (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The integration between the Conceptual Metaphor Theory (CMT) and the pragmatic aspect of the metaphor usage has resulted in the emergence of the Critical Metaphor Analysis (CMA) approach to examine metaphors in public discourse. By applying this approach, the present study explores the types of metaphors in Ustadz Hanan Attaki (henceforth UHA) and Ustadz Abdul Somad (Henceforth UAS) both English and Indonesian speech corpora on economic discourses and their possible latent ideologies. The results also indicate that some (linguistic) realizations of conceptual mappings of the metaphors in UHA and UAS’ corpus are used to evoke the emotion and the soul of their audiences. Further, the current study also shows that both UHA and UAS share similar collectivism/jama’ah ideological values manifested through the journey and battle metaphors dataset.